Research progress in aluminum-based anti-icing surfaces - HE Zhi-wei; SHEN Zi-hang; QIU Huan-yi; CHEN Jia-hao; LIANG Li-jun; WANG Jian-jun (Cailiao gongcheng, 2021)
Aluminum and aluminum alloys are widely utilized metal materials. When they are used as surfaces working below 0℃, the anti-icing protection is of great importance for the operation safety of facilities. Two types of aluminum-based anti-icing surfaces were introduced, including superhydrophobic surfaces and organic lubricating layers. First, methods of preparation of micro/nanostructures and surface energy lowering for aluminum-based anti-icing surfaces were discussed, followed by the summarization of their advantages and disadvantages. Then, the characterization of anti-icing performances for aluminum-based surfaces was introduced, including delay of droplets freezing and ice adhesion strength, by which the difference of the anti-icing performance of aluminum-based surfaces can be evaluated. In the end, it was put forward that the future research should be focused on the durability and sustainability of aluminum-based anti-icing surfaces during icing/de-icing cycles.